Transgresivnost v znanosti, literaturi in humanistiki - Kos, Dejan (Primerjalna književnost, 2012)
The concept of transgressiveness first appeared during the Early Modern Age, and can since then be found in legal, theological, scientific and philosophical discourses. It predominantly refers to phenomena that transcend the limits of the ordinary, shift from expected practices and defy the fundamental conventions of communication, society or morality. Although its meaning is not sharply defined, there is no doubt that transgressiveness is linked to the vital functional dimensions of cognitive and social systems, since establishing, controlling and eliminating unconventional states is part and parcel of the fundamental mechanisms that ensure adaptability in complex environments. Of course, these mechanisms manifest themselves in various ways in different social systems such as science, the humanities and literature.
Keywords: transgresivnost; znanost; science; literature; književnost; literarni sistemi; humanistika; epistemologija; epistemology; kontingenca